PENGARUH MODEL GUIDED DISCOVERY LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS X SMA NEGERI 8 SURAKARTA TAHUN PELAJARAN 2014/2015 - Widura, Hakim Surya; Karyanto, Puguh; Ariyanto, Joko (BIO-PEDAGOGI, 2015)
The aim of this research to know the influence of Guided Discovery Learning with case study of students' critical thinking skills system material. Research was Quasi Experiment (quasi-experimental) with research design Posttest Only with Non-equivalent Control Group Design. The research population was all students of ten (X) grade SMA Negeri 8 Surakarta academic year 2014/2015. Sampling technique in the study is cluster sampling, with samples of the two classes, there are ten grade (X) MIA 2 with 26 students as the number of experimental class and ten (X) MIA 4 with 24 students a class control. Treatment in the experimental class is the application of the learning model of Guided Discovery Learning with case study and in control class applied conventional learning model with varied lectures. The technique of collection data was using test method (essay) and non- test (documentation and observation). Hypothesis testing is done by using a t-test. The results showed that the average value of the critical thinking skills of students in the experimental class was higher than the control class, which is 79.07 in experimental class and 68.2 in the control class. The results show the significant value of t-test is 0.035 (sig. <0.05), so it can be said that there are significant differences in the critical thinking skills between experimental class with control class. The research has conclusion that the model of guided discovery learning gives significant effect on students' critical thinking  skills  for  ten (X)  grade  MIA  SMA  Negeri  8  Surakarta  in  academic  year 2014/2015. Keywords: guided discovery learning, critical thinking skills